The Role of Classroom Emotional Climate in Predicting Student Engagement and Learning Satisfaction - Muhammad Ridwan (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2026)
The emotional climate of university classrooms has emerged as an important factor influencing student engagement and learning experiences. This study explores how classroom emotional climate influences student engagement and learning satisfaction among undergraduate students. The study involved 312 undergraduate students enrolled in social science courses at University of Copenhagen. Students completed validated scales measuring perceived classroom emotional climate, engagement, and learning satisfaction. Data were analyzed using multiple regression and path analysis. Classroom emotional climate significantly predicted student engagement (β = 0.483, p < 0.001) and learning satisfaction (β = 0.451, p < 0.001). Engagement also significantly predicted satisfaction (β = 0.372, p < 0.001), suggesting a partial mediation relationship. Positive classroom emotional climates enhance student engagement and improve overall learning satisfaction. Universities should support teaching practices that foster supportive and emotionally positive classroom environments.